Characterization of the lipidomic profile of clam Meretrix petechialis in response to Vibrio parahaemolyticus infection. Issue 134 (March 2023) - Zhang, Shujing; Jiao, Shuang; Liu, Dongwu; Xie, Changjian; Dong, Yuling; Zheng, Kang; Liu, Baozhong; Pang, Qiuxiang
Abstract: Vibrio parahaemolyticus is a devastating pathogen of clam Meretrix petechialis, which brings about huge economic losses in aquaculture breeding industry. In our previous study, we have found that Vibrio infection is closely associated with lipid metabolism of clams. In this study, an untargeted lipidomics approach was used to explore the lipid profiling changes upon Vibrio infection. The results demonstrated that the hepatopancreas of clams was composed of five lipid categories including fatty acyls, glycerolipids, glycerophospholipids, sphingolipids and sterol lipids. And the content of lipid classes altered during Vibrio infection, implying that Vibrio infection altered intracellular lipid homeostasis in clams. Meanwhile, a total of 200 lipid species including 82 up-regulated and 118 down-regulated significantly were identified in response to Vibrio infection, of which ceramide (Cer), phosphatidylcholine (PC) and triglyceride (TG) accounted for the largest proportion. Notably, all Cers showed a significantly decreased trend while nearly all TG species were increased significantly during Vibrio infection, which suggested that Cer and TG could be determined as effective biomarkers. Furthermore, these differentially expressed lipid species were enriched in 20 metabolic pathways and sphingolipid metabolism was one of the most enriched pathways. These results evidenced how the lipid metabolism altered in the process of Vibrio infection and opened a new perspective on the response of marine bivalves to pathogen infection. Highlights: Relationship between Vibrio infection and lipid metabolism in the clam Meretrix petechialis was investigated. Vibrio infection altered the lipid homeostasis in clams. Some metabolic pathways were explored in Vibrio -infected clams.